Implementasi Metode Design Science Research (DSR) pada Monitoring Server Voip Berbasis Web dengan Pendekatan Agile untuk Optimalisasi Kinerja Sistem (Studi Kasus: PT. XYZ) - Dimas, Dimas Adjie; Zakaria, Hadi (JURNAL FASILKOM, 2026)
PT. XYZ is a telecommunications technology company that has been providing cloud-based communication services, such as Cloud PBX, VoIP Telephony, Cloud Call Centers, and integrated Omni-Channel CRM systems, since 2013. The scope of this research is focused on infrastructure optimization through the development of a centralized monitoring system to manage thousands of call history records and server performance data. The background of this study is driven by the increasing number of clients and system complexity, which has rendered manual monitoring methods ineffective. This inefficiency leads to risks such as limited performance visibility, potential human error, and undetected security threats. Consequently, this research aims to build an innovative artifact in the form of a web-based VoIP server monitoring system capable of providing automated, centralized, and real-time monitoring. The methodology employed is Design Science Research (DSR) combined with an Agile approach to create a system that is adaptive to the company's changing needs. The system was developed using the Laravel framework, Python for backend processing, Chart.js for interactive visualization, and MySQL for telemetry data storage. The collected monitoring data includes CPU, memory, and disk utilization, connectivity status, and essential port openness, gathered by agents every minute. Implementation results indicate that the system successfully presents current server conditions, detects resource usage anomalies, and provides automated notifications during service disruptions. In conclusion, this system significantly improves operational efficiency, service security, and the quality of VoIP server monitoring, while strengthening the company's position as a reliable and trusted cloud-based communication solution provider in Indonesia.